Competency Based Teacher Education Toward a Consensus. - National Advisory Council on Education Professions Development, Washington, DC.; National Advisory Council on Education Professions Development, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Competency based teacher education (CBTE) has generated much controversy. Among its accomplishments, CBTE has provided a visible alternative to conventional teacher education programs. It has forced developers of programs to think beyond the traditional programs. The controversy has required educators to look for new ways of improving educational programs. CBTE provides an emphasis on the real world of schools and their specific needs and objectives and an emphasis on explicitness and openness which has demanded new kinds of communication both within and outside the profession. CBTE is recognized to have major problems, both substantive and political. One of these is that it is not applicable to all content areas. Also, there is a recognized difficulty in first determining competencies required and then finding effective ways of teaching them. Finally, measurement is always a problem. Despite these concerns, CBTE is viewed as a promising alternative form of teacher education. (Several specific recommendations concerning CBTE are included in the Council's report.) (JMF)
Availability: National Advisory Council on Education Professions Development, 1111 20th Street, N.W., Suite 308, Washington, D.C. 20036 (single copies free).
ERIC Note: Appendix B may reproduce poorly due to type size.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competency Based Teacher Education; Educational Change; Educational Objectives; Educational Philosophy; Educational Programs; Teacher Education; Teacher Education Curriculum; Reports, Research